GURU PENDIDIKAN AGAMA ISLAM SEBAGAI AGEN MODERASI BERAGAMA DI LEMBAGA PENDIDIKAN FORMAL - Hamzah Irfanda; Syifa Ulinnas; Aldi Saputra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
The growing prevalence of intolerance, radicalism, extremism, and social polarization among young people has become a major challenge for the education sector, particularly due to the rapid flow of digital information that facilitates the dissemination of exclusive religious ideologies. In this context, Islamic Religious Education (IRE) teachers play a strategic role as agents of religious moderation by internalizing the values of Islam Rahmatan lil 'Alamin (Islam as a mercy to all creation). This study aims to examine the role of IRE teachers as agents of religious moderation in formal educational institutions in Indonesia. The study employs a qualitative approach using a literature review method through the analysis of relevant scholarly sources. The findings indicate that IRE teachers serve as role models, educators, and facilitators in fostering the values of tolerance, inclusivity, nonviolence, and respect for diversity. The implementation of religious moderation contributes to the creation of a harmonious educational environment and strengthens national unity. Despite challenges such as the spread of extremist ideologies and limited resources, efforts to enhance teachers' competencies, strengthen curricula that are responsive to contemporary developments and local wisdom, and promote collaboration among stakeholders can optimize the role of IRE teachers in advancing moderate and inclusive Islamic education. This study is expected to provide a conceptual contribution to strengthening the implementation of religious moderation within educational settings.